MyGrammarLab. Intermediate B1/B2. With Key - Foley M. Mark (Harlow, Pearson, 2018)
Think all grammar courses are the same? Think again... MyGrammarLab is a unique blend of book, online and mobile resources that ensures you have all the information and practice you need to master English grammar. Easy-to-understand explanations using the Longman Defining Vocabulary -a simple vocabulary of just 2000 words. Topic-based modules and natural examples showing grammar in use. Information on common errors and how to avoid making them.Information on the pronunciation of grammar items. Practice exercises for every unit. Review sections to consolidate learning. Exit tests to check nderstanding. Grammar Check and full glossary of grammar terms for quick grammar reference.